Contaminación ambiental y salud de las mujeres - Carme Valls-Llobet (Investigaciones Feministas, 2010)
Environmental pollution can enter the human body via the respiratory or digestive systems or through the skin. As pollution enters the body via air, water, food and cosmetics, we often do not realize that we are exposed to toxic products which may be prejudicial to our health. Many toxic insecticides, solvents and heavy metals can accumulate in our bodies, and in particular in women's bodies due to their higher concentration of fat cells. Women´s bodies can act as chemical bio accumulators and suffer consequences such as changes in reproductive health and the appearance of new illnesses such as fibromyalgia, multiple-chemical sensitivity, chronic fatigue syndrome and an increase in breast cancer. The growing influence of environmental pollution on women's health means that that eco-feminism can no longer neglect the need for research in this area.